Determinants of Cardiometabolic Risk Factors in the First Decade of Life: A Longitudinal Study Starting at Birth. Issue 3 (March 2018) - Lurbe, Empar; Aguilar, Francisco; Álvarez, Julio; Redon, Pau; Torró, Maria Isabel; Redon, Josep
Abstract : The present prospective study assessed the association of birth weight (BW) and growth pattern on cardiometabolic risk factors in a cohort followed from birth to 10 years of age. One hundred and forty-five subjects (73 girls) who fulfilled the inclusion criteria and had all their data recorded at birth and at 5 years were enrolled. Of these, 100 (52 girls) also recorded data at 10 years. Anthropometric measurements, office and 24-hour blood pressure, and metabolic parameters were obtained. At 5 years, both BW and current weight were determinants of blood pressure and metabolic parameters; however, as the subjects got older, the impact of body size increased. Higher BW and maternal obesity increased the risk of becoming obese at 5 years while this was reduced if breastfeeding. Maternal obesity was the only factor associated with becoming obese at 10 years. Twenty-two children at 10 years had insulin values ≥15 U/L, some of whom were persistent from 5 years while in others it increased afterward. Subjects with insulin values ≥15 U/L showed significant higher values of office systolic blood pressure, triglycerides, and uric acid and lower values of high-density lipoprotein than did those with normal insulin values. Highest weight gain from 5 to 10 years and lowest BW were the main determinants of high insulin levels. In conclusion, although BW was a proxy of the events during fetal life and projected its influence later, the influence of gaining weight was a key determinant in the risk to develop obesity and metabolic abnormalities. Abstract : Supplemental Digital Content is available in the text.